Endosonography-Guided Caudate Lobe Liver Abscess Drainage: A Case and Review of Methods - Zanwar, Shankar; Agrawal, Amit (Journal of Digestive Endoscopy, 2022)
There are only 11 cases of caudate lobe liver abscess drainage described in the published literature. We present a case of liver abscess drainage done by endosonography (EUS) and review of various EUS-guided liver abscess drainage techniques and endoprostheses. Here we have aimed at reviewing the data for paving the way for the development of a consensus for liver abscess drainage.
Keywords: endosonography; liver abscess drainage; percutaneous drainage